The effect of computer mouse mass on target acquisition performance among action video gamers. - Conroy, Eoin; Toth, Adam J.; Campbell, Mark J. (Applied Ergonomics, 2022)
Advances in human performance have shifted research attention from individuals towards understanding the effects that equipment can have on their performance. In esports, the effect of gaming peripherals on performance has only recently been explored. In this study, we investigated the effect of computer mouse mass on gaming skill. 72 video game players performed a target acquisition task, a pertinent composite skill in first-person shooter (FPS) video games, while using computer mice that varied only by their mass (50g, 60g, 90g & 100g). Results showed that participants were 4% faster and 9% more accurate with 50g, 60g, and 90g mice compared to the 100g mouse. They were also 34% more accurate and 14% more precise when using lower control-display gain and preferred lighter mice (50g and 60g) when performing the skill at a lower control-display gain. Taken together, using a lighter mouse at lower sensitivity may augment target acquisition performance among video gamers.